Development of growth mindset in higher education in support of the World-Class University - Setiawan, Risky; Dewi, Radeni Sukma Indra; Zainul, Rahadian (Institute of Advanced Engineering and Science, 2024)
This study aims to develop a tool to measure the growth mindset of university lecturers, which is associated with performance and professionalism in institutions, especially at Universitas Negeri Yogyakarta (UNY) to go to a World-Class University (WCU). This research is a research and development (R&D) research with a quantitative approach measuring the quality of university growth mindset instruments. The measuring tool developed is a questionnaire using the confirmatory factor analysis (CFA) method. The results of each indicator are analyzed and integrated with structural equation modeling (SEM). The results of the growth mindset study of the academic community at UNY. The growth mindset instrument construct for the academic community is qualified to measure the ability of growth mindset from lecturers. The results show that the developed instruments show a valid and reliable construct. Advanced analysis by multiple regression method with path analysis shows that the academic level is the moderate variable with the most influence on the growth mindset path analysis model. Increasing the academic level will optimize the growth mindset of lecturers; performance will evolve.